(untitled) (International Journal of Food and Nutritional Sciences, 2021)
Neurological diseases often manifest through various motor impairments, and gait analysis has proven to be a valuable tool for their early detection and prediction. Cerebellar ataxia, characterized by uncoordinated movements and postural instability, poses significant challenges for both patients and clinicians. This study focuses on predicting cerebellar ataxia based on impaired gait analysis, specifically targeting foot position abnormalities, through the application of an ensemble approach.